Geospatial technologies and the nursing process in a sentinel unit: experience report - Jane Kelly Oliveira Friestino; Magda Fantin; Thaísa Carla Sfredo; Grasiele Fátima Busnello (Universidade Federal de Santa Maria, 2018)
Aim: to report a research incorporation of suspected cases of Dengue, Zika virus and Chikungunya to the nursing process in a Sentinel Surveillance unit of Zika virus. Method: experience report which used geospatial technologies as teaching-learning tools during Supervised Curricular Internship of a nursing undergraduate course, in a sentinel Surveillance unit. All notifications of the cases were gathered and the geocoding of the individuals' residence was done, contributing for the nursing process in a Sentinel Surveillance unit. Results: new information were produced about the suspected individuals' addresses, it was noted that the attended population reside mostly in a region, which already has service recommended for. Conclusions: the experience contributed to a priorities definition for actions related to cases of Dengue, Chikungunya and mainly for the Zika virus, pointing out new possibilities for the use of geospatial technologies.